2016
DOI: 10.1177/1074248416644343
|View full text |Cite
|
Sign up to set email alerts
|

Salts of Clopidogrel: Investigation to Ensure Clinical Equivalence: A 12-Month Randomized Clinical Trial

Abstract: The efficacy and safety of CB administered for 12 months for the secondary prevention of atherothrombotic events are similar to that of CHS. (Salts of Clopidogrel: Investigation to ENsure Clinical Equivalence, SCIENCE trial; ClinicalTrials.gov Identifier:NCT02126982).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…In this work it was revealed that at 12 months of follow-up, the clinical endpoint had occurred in a relatively low number of patients, below 5% of the total number of ACS patients who participated in the study, without any differences between genders, or between those patients living in mainland urban areas or on the islands. As for the all-cause mortality rate, this was low, probably due to the short-term follow-up period, the result of which was in accordance with our previously published study using the same generic clopidogrel formulation [ 16 ]. Furthermore, the use of the generic clopidogrel besylate was quite high (81–90%) in both urban and insular areas.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this work it was revealed that at 12 months of follow-up, the clinical endpoint had occurred in a relatively low number of patients, below 5% of the total number of ACS patients who participated in the study, without any differences between genders, or between those patients living in mainland urban areas or on the islands. As for the all-cause mortality rate, this was low, probably due to the short-term follow-up period, the result of which was in accordance with our previously published study using the same generic clopidogrel formulation [ 16 ]. Furthermore, the use of the generic clopidogrel besylate was quite high (81–90%) in both urban and insular areas.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, it is important that any efficacy or safety concern arising from the use of generic clopidogrel in CVD patients should be referred to the specific product used. In this regard, our previous studies have demonstrated that the pharmacodynamic potency as well as clinical efficacy and safety profile of the generic clopidogrel used in the present study are similar to those of the original drug [16,[22][23][24]. In the present work, the 12-month composite clinical endpoint remained quite low, with the use of generic clopidogrel being at a high level, while multivariate analysis revealed that original and generic forms of clopidogrel did not present any significant differences in terms of the examined efficacy outcome (Table II).…”
Section: Protective Effect Harmful Effectsupporting
confidence: 65%
See 1 more Smart Citation